Vulnerable Baby Scale: A validity and reliability study - Celik, Melike Yavas; Cigdem, Zerrin (KARE PUBL, 2020)
Objectives: This study aims to evaluate the validity and reliability of the Vulnerable Baby Scale ( VBS) in Turkish. Methods: This methodological study was conducted between December and July, 2019 with 371 mothers having babies between the ages of 1 week and 4 months. Results: Language validity of VBS was determined to be appropriate after translation-back translation and expert opinion. The sample adequacy calculated for the VBS was evaluated as very good Kaiser Mayer Olkin (KMO=0.851, X-2=665.065). The Confirmatory Factor Analysis (CFA) determined that the VBS maintained its single-factor structure of 10 items, factor loadings of the VBS items ranged between 0.38 and 1.16 and the CFA fit index values were within acceptable limits/perfect fit limits. In this study, Cronbach's alpha reliability coefficient was found to be 0.84. The two half reliability levels of the scale were evaluated as 0.85. A moderate positive correlation was found between the Edinburgh Postpartum Depression Scale (EPDS) and the VBS (r=0.32). Test-retest results showed a weak positive and significant relationship (r=0.99). Conclusion: It was concluded that Turkish version of the VBS had sufficient internal reliability and validity to be able to evaluate the perception of "Vulnerable Baby Syndrome".
Keywords: Reliability; validity; vulnerable baby syndrome